2022
DOI: 10.3389/fcell.2022.1011657
|View full text |Cite
|
Sign up to set email alerts
|

In the pursuit of new social neurons. Neurogenesis and social behavior in mice: A systematic review

Abstract: Social behaviors have become more relevant to our understanding of the human nervous system because relationships with our peers may require and modulate adult neurogenesis. Here, we review the pieces of evidence we have to date for the divergence of social behaviors in mice by modulation of adult neurogenesis or if social behaviors and the social environment can drive a change in neurogenic processes. Social recognition and memory are deeply affected by antimitotic drugs and irradiation, while NSC transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…In the current study, we demonstrated that MK-801-treated zebrafish displaying impaired social interaction and increased anxiety levels, two common co-existing conditions in several neuropsychiatric illnesses ( Allsop et al, 2014 ), were characterized by defective neurogenesis in the molecular level. In support, antimitotic drugs have been correlated with disrupted social recognition and memory (for refs García-Gómez et al, 2022 ). The above results are of particular interest since previous studies have also reported the presence of deficits in social communication and increased anxiety levels along with neurogenesis defects in various rodent models of neurological and neuropsychiatric diseases ( Miller and Hen, 2015 ; Hong et al, 2019 ; Gioia et al, 2022 ), thus further validating this zebrafish pharmacological model as a useful tool for investigating the mechanistic link between dysregulated neurogenesis and comorbid social deficit and anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 95%
“…In the current study, we demonstrated that MK-801-treated zebrafish displaying impaired social interaction and increased anxiety levels, two common co-existing conditions in several neuropsychiatric illnesses ( Allsop et al, 2014 ), were characterized by defective neurogenesis in the molecular level. In support, antimitotic drugs have been correlated with disrupted social recognition and memory (for refs García-Gómez et al, 2022 ). The above results are of particular interest since previous studies have also reported the presence of deficits in social communication and increased anxiety levels along with neurogenesis defects in various rodent models of neurological and neuropsychiatric diseases ( Miller and Hen, 2015 ; Hong et al, 2019 ; Gioia et al, 2022 ), thus further validating this zebrafish pharmacological model as a useful tool for investigating the mechanistic link between dysregulated neurogenesis and comorbid social deficit and anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 95%